1994
DOI: 10.1002/ana.410360613
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q10 and nicotinamide block striatal lesions produced by the mitochondrial toxin malonate

Abstract: A potential mechanism of neuronal injury in neurodegenerative diseases is a defect in energy metabolism that may lead to slow excitotoxic neuronal death. Consistent with this possibility, we showed that specific inhibitors of the electron transport chain produce excitotoxic lesions in vivo. In the present study we examined whether agents that improve energy metabolism can block lesions produced by the mitochondrial toxin malonate. Striatal lesions produced by the complex II inhibitor malonate were blocked in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
101
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 185 publications
(109 citation statements)
references
References 31 publications
8
101
0
Order By: Relevance
“…Several human studies have suggested that CoQ supplementation ameliorated mitochondria-related abnormalities (Bresolin et al 1990;Morisco et al 1993;Hofman-Bang et al 1995) and age-related symptoms of heart failure and hypertension as well as neurodegenerative diseases including amyotrophic lateral sclerosis, Huntington's disease, and diabetic neuropathy (Baggio et al 1993;Beal et al 1994;Koroshetz et al 1997;Ferrante et al 2002;Rosenfeldt et al 2003Rosenfeldt et al , 2007Hyson et al 2010). Furthermore, several investigations suggest that supplementation of CoQ could have effects similar to caloric restriction or antioxidant-rich foods.…”
mentioning
confidence: 99%
“…Several human studies have suggested that CoQ supplementation ameliorated mitochondria-related abnormalities (Bresolin et al 1990;Morisco et al 1993;Hofman-Bang et al 1995) and age-related symptoms of heart failure and hypertension as well as neurodegenerative diseases including amyotrophic lateral sclerosis, Huntington's disease, and diabetic neuropathy (Baggio et al 1993;Beal et al 1994;Koroshetz et al 1997;Ferrante et al 2002;Rosenfeldt et al 2003Rosenfeldt et al , 2007Hyson et al 2010). Furthermore, several investigations suggest that supplementation of CoQ could have effects similar to caloric restriction or antioxidant-rich foods.…”
mentioning
confidence: 99%
“…Beal et al (1994) injected malonic acid in striatum of laboratory animals, and found that this procedure induced depletion of ATP and an increase in lactic acid. The administration of CoQ 10 in animals was able to mitigate the depletion of ATP induced by malonate while minimizing the increase in concentrations of lactate.…”
Section: Coenzyme Q 10 and The Central Nervous Systemmentioning
confidence: 99%
“…CoQ 10 significantly attenuates the depletion of ATP and malonate-induced increases of lactate in brain mitochondria of rats (Beal et al, 1994). Supplementation of CoQ 10 in rats increased the endogenous content of CoQ 10 in the brain and provided antioxidant protection against free radical generation (Kwong et al, 2002; Lenaz et al, 1999;Rauscher, Sanders, Watkins, 2001;Somayajulu et al, 2005).…”
Section: Alzheimer's Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…We studied the effects of administration of CoQ 10 on lesions produced by mitochondrial toxins. Oral administration of C0Q10 produced dose-dependent neuroprotective effects against malonate induced striatal lesions as well as depletions of ATP and increases in lactate concentrations [84]. Administration of CoQ 10 produced significant protection against dopamine depletions induced by MPTP administration [85].…”
Section: Coenzyme Qio and Neuroprotectionmentioning
confidence: 99%